Acceptability of three novel HIV prevention methods among Puerto Rican male and transgender female sex workers - Giguere, Rebecca (AIDS Behav, 2016)
Male and transgender female (TGF) sex workers need HIV-prevention methods they can control and incorporate easily in their work. We explored acceptability of the use of the HIV self test with clients, oral pre-exposure prophylaxis (PrEP), and rectal microbicide gel among 12 male and TGF sex workers in Puerto Rico. At baseline, we measured likelihood of use of each method. Five sex workers also completed a 12-week study of rectal microbicide placebo gel use prior to receptive anal intercourse with clients and explored in interviews how each method could be incorporated into their work. Most were interested in a rectal microbicide gel and able to use it covertly with clients. Challenges to using the HIV self test with clients included breach of confidentiality and violent situations. They expressed some interest in oral PrEP, but had concerns about side effects. Rectal microbicides may work well for this population.